Specification for nickel-iron-chromium-molybdenum-titanium heat-resisting alloy billets, bars, forgings and parts (Ni/Co 42.5, Cr 12.5, Mo 5.8, Ti 3.0, Fe remainder). (9th March 1973) - British Standards Institution,
No abstract available